L-type Calcium Channels are Involved in Iron-induced Neurotoxicity in Primary Cultured Ventral Mesencephalon Neurons of Rats - Xu, Yu-Yu (Neurosci Bull, 2019)
In the present study, we investigated the mechanisms underlying the mediation of iron transport by L-type Ca(2+) channels (LTCCs) in primary cultured ventral mesencephalon (VM) neurons from rats. We found that co-treatment with 100 µmol/L FeSO(4) and MPP(+) (1-methyl-4-phenylpyridinium) significantly increased the production of intracellular reactive oxygen species, decreased the mitochondrial transmembrane potential and increased the caspase-3 activation compared to MPP(+) treatment alone. Co-treatment with 500 µmol/L CaCl(2) further aggravated the FeSO(4)-induced neurotoxicity in MPP(+)-treated VM neurons. Co-treatment with 10 µmol/L isradipine, an LTCC blocker, alleviated the neurotoxicity induced by co-application of FeSO(4) and FeSO(4)/CaCl(2). Further studies indicated that MPP(+) treatment accelerated the iron influx into VM neurons. In addition, FeSO(4) treatment significantly increased the intracellular Ca(2+) concentration. These effects were blocked by isradipine. These results suggest that elevated extracellular Ca(2+) aggravates iron-induced neurotoxicity. LTCCs mediate iron transport in dopaminergic neurons and this, in turn, results in elevated intracellular Ca(2+) and further aggravates iron-induced neurotoxicity.